Correction: Storm-Clouds on the Horizon: John Ruskin and the Emergence of Anthropogenic Climate Change - Jesse Oak Taylor (19, 2019)
This article details a correction to the article: Taylor, J.O., 2018. Storm-Clouds on the Horizon: John Ruskin and the Emergence of Anthropogenic Climate Change. 19: Interdisciplinary Studies in the Long Nineteenth Century, (26) DOI: http://doi.org/10.16995/ntn.802